Should diagnostic hysteroscopy be performed routinely following thermal balloon endometrial ablation? A case report of thermal bowel injury and literature review - Hazem Al-Mandeel (IMR Press, 2021)
Although thermal balloon endometrial ablation (TBEA) is an effective and easy technique, it can cause serious complications, including bowel injury, if perforation occurs. In this paper, a case of thermal bowel injury caused by the Thermablate Endometrial Ablation System is presented with a review of previous literature on such complications. Based on this case and expert recommendations, users are advised to follow established protocols, including hysteroscopy just prior to the insertion of the TBEA catheter to exclude prior uterine perforation from the uterine sound or curettage, and an additional hysteroscopy after completion of the ablation as the final step to ensure that a perforation has not occurred.